Pollen morphology of the Ephedra (Ephedraceae) species distributed in Mexico - Galván Escobedo, Iris Grisel; López-Mata, Lauro; Zepeda Rodríguez, Armando; Pasos Nájera, Francisco; Rosas Pérez, Irma (Instituto de Ecología, A.C., 2023)
Background and Aims: The Ephedra genus contains nearly 50 species distributed in semi-arid regions of the world. Mexico contains eight of these species: Ephedra antisyphilitica, E. aspera, E. californica, E. compacta, E. nevadensis, E. pedunculata, E. torreyana and E. trifurca. The botanical affinities of Ephedripites fossil pollen are difficult to assign due to lack of detailed data on pollen morphology of extant Ephedra species distributed in Mexico. The objective of this work was to characterize the pollen morphology of the eight Ephedra species distributed in Mexico as well as to detect the distinctive morphological variables of each species.Methods: Pollen grains were taken from herbarium specimens and processed with the acetolysis technique. Eight morphological variables were reviewed with both photonic microscopy and scanning electron microscopy. All variables were analyzed with univariate and multivariate statistical techniques. Key results: The variables of morphological importance were number of plicae and distance among plicae, and plica form and pseudosulcus form. Of these, the distance among plicae is not a variable commonly considered relevant in studies of pollen morphology of Ephedra. The pseudosulcus form accounted for the most pollen variation provided it is linked to presence or absence of pseudosulcus ramifications. Ephedra species were grouped into four classes: I) E. aspera, E. compacta and E. pedunculata; II) E. californica and E. trifurca; III) E. antisyphilitica and E. torreyana; and IV) E. nevadensis.Conclusions: Multivariate statistical methods allowed us to jointly analyze qualitative and quantitative characters of the pollen of the Ephedra species from Mexico and group them into classes based on their pollen morphology. This serves as a reference to assign botanical affinities with current species that have typical Ephedroid pollen recorded in some paleobasins of Mexico.